Teaching Language As Action in the ELA Classroom Decentralizing the Metropolis - Beach, Richard; Beauchemin, Faythe (Routledge, 2019)
This book explores English language arts instruction from the perspective of language as "social actions" that students and teachers enact with and toward one another to create supportive, trusting relations between students and teachers, and among students as peers. Departing from a code-based view of language as a set of systems or structures, the perspective of languaging as social actions takes up language as emotive, embodied, and inseparable from the intellectual life of the classroom. Through extensive classroom examples, the book demonstrates how elementary and secondary ELA teachers can apply a languaging perspective. Beach and Beauchemin employ pedagogical cases and activities to illustrate how to enhance students' engagement in open-ended discussions, responses to literature, writing for audiences, drama activities, and online interactions. The authors also offer methods for fostering students' self-reflection to improve their sense of agency associated with enhancing relations in face-to-face, rhetorical, and online contexts
Relational Framing of Events: Expecting the Unexpected
Keywords: Language arts (Secondary); English language / Study and teaching (Secondary); Interaction analysis in education; Teacher-student relationships